Evaluation of the effectiveness of biofeedback therapy for functional constipation in children - Jarzebicka, Dorota; Sieczkowska, Joanna; Dadalski, Maciej; Kierkus, Jaroslaw; Ryzko, Jozef; Oracz, Grzegorz (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Defecation disorders are one of the most common problems in pediatric gastroenterology. Treatment includes changes in the diet, pharmacotherapy, and biofeedback therapy. The aim of the present study was to evaluate the effectiveness of biofeedback therapy as assessed by clinical improvement as well as by changes in manometric parameters in children with constipation and pelvic floor dyssynergia (PFD). Materials and Methods: A total of 44 children with constipation and PFD hospitalized between 2000 and 2015 were enrolled in this retrospective study. All patients underwent anorectal manometry, and in case of diagnosed PFD, the patient qualified for biofeedback therapy. Amplitudes between extreme and basic pressures during defecation maneuvers in the first and last sessions as well as the difference between them were compared between groups with and without clinical improvement after the last session. Results: A clinical improvement was achieved in 38 (86%) patients. There were no significant differences found in the amplitudes in the first session (mmHg), 94, 65, 115 vs. 112, 55, 170 (median, first quartile, third quartile, respectively; NS: not significant); last session, 36, 27, 52 vs. 41, −38, 66, respectively; or between them, 71, 11, 124 vs. 81, 17, 109, respectively, in the group with versus the group without clinical improvement, respectively. Conclusion: Biofeedback therapy has high clinical efficacy, and despite the lack of manometric improvement, it should be used as a treatment method in children in whom dietary and pharmacological procedures do not work, even if we consider the exercises more as a form of psychological training.